FINANCING OF EDUCATION AND SCIENCE UNDER THE CONDITIONS OF EDUCATIONAL REFORMS - Kondur , O.S.; Tsiupa , O.P. (The actual problems of regional economy development, 2018)
The reform of educational industry of Ukraine consists in forming of new generation of specialists for the national and international economy. The results of transformations in education should affect the development of the economy and society as a whole. The basic stages of educational reform are analysed in the article. It is described how the laws provide for financial and material and technical providing of the system of education and science. An example of the formation of expenditures in the State Budget for 2018 the impact of educational transformations on the financing of the educational system.